Towards a potent and rapidly reversible Dexmedetomidine-based general anesthetic. - Zheng Xie; Robert Fong; Aaron P Fox (PLoS ONE, 2023)
In conclusion Our results suggest that Dex supplemented with a low dose of a second agent creates a potent anesthetic that is rapidly reversed by atipamezole and caffeine.